Pengaruh Environment, Social and Governance Disclosure terhadap Kinerja Perusahaan - Gustin Ningwati; Ratna Septiyanti; Neny Desriani (Goodwood Akuntansi dan Auditing Reviu, 2022)
Purpose: This study aims to empirically examine the effect of ESG disclosure on the performance of companies listed as star companies listing on the ESG market for the 2017-2021 period. Research methodology: The approach method used is a quantitative approach. The analytical method used is descriptive statistical test, classical assumption test and multiple regression analysis test. The sample selection used was porposive sampling with the number of data samples used as many as 30. Results: The results showed that ESG Disclosure had no effect on ROE and ESG Disclosure had a significant negative effect on Tobin's Q. Limitations: A limitation in this study is the variables used only in the scope of performance. financial and research period and the sample used is very limited. Contribution: This research can be used by stakeholders as consideration for making decisions as well as for academics or other researchers as reference material. This research is useful to find out empirically how the effect of ESG disclosure on company performance so that it can have a positive impact on Indonesia's economic growth.